Understanding Trust in Organizations A Multilevel Perspective (Taylor & Francis, 2021)
network trust, trust, second-hand trust, prototrust, relational trust, network theory, mechanism, indicators, contingencies, tie strength, social distance, network closure, vertical network differentiation, governance veracity, identity authenticity, swift trust
English
Keywords: Occupational & industrial psychology; Organizational theory & behaviour; Personnel & human resources management; Psychology; network trust, trust, second-hand trust, prototrust, relational trust, network theory, mechanism, indicators, contingencies, tie strength, social distance, network closure, vertical network differentiation, governance veracity, identity authenticity, swift trust